A modified Wingate test for measuring anaerobic work of the upper body in junior rowers. Issue 4 (December 1986) - Koutedakis, Y; Sharp, N C
Abstract : Eight elite junior oarsmen (ER) and sixteen club level rowers (CR) were tested for upper body strength (trunk, arms) and for mean, peak and minimum power outputs using the Double-Arm Anaerobic Work Test (DAAWT). This test is a modified version of the original Wingate test whereby athletes can be tested using trunk and both arms simultaneously. Multiple Discriminant Analysis was used to determine if the DAAWT variables alone were sensitive enough to discriminate between the two groups. Additionally, Pearson's correlation coefficients and ANOVA were employed. Results indicate that mean power and power difference expressed in absolute values (Watts) could successfully classify junior oarsmen into appropriate groups (91.8%, P less than 0.001). In addition, there was a fairly high correlation (r = 0.81) between mean power and strength in the ER. The strongest ER demonstrated the least fatigue while highly significant differences between the groups in most of the other variables examined have also been demonstrated.